2008
DOI: 10.1353/hpu.2008.0002
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Anticoagulation Control: Do Race and Language Matter?

Abstract: No studies have evaluated the quality of anticoagulation control among populations characterized by low socioeconomic status, diverse racial and ethnic backgrounds, or limited English proficiency. We conducted a retrospective cohort study to evaluate the effects of race/ethnicity and language on anticoagulation outcomes among patients (N=864) receiving continuous anticoagulation services at a university-affiliated public hospital. White/non-Hispanic patients made up 24%, Asian/Pacific Islanders 33%, Hispanics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Administrative claims data were the most common sources of primary ADE detection, used in 37.5 % (15/40) of studies [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Chart review was used as a primary ADE detection method in 35 % (14/40) of studies [8,[24][25][26][27][28][29][30][31][32][33][34][35][36], and survey or patient/ parent report was used in 27.5 % (11/40) of the studies [27,32,33,[37][38][39][40][41][42][43][44]. Direct documentation by research staff was used by three studies (7.5 %) [45][46][47].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Administrative claims data were the most common sources of primary ADE detection, used in 37.5 % (15/40) of studies [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Chart review was used as a primary ADE detection method in 35 % (14/40) of studies [8,[24][25][26][27][28][29][30][31][32][33][34][35][36], and survey or patient/ parent report was used in 27.5 % (11/40) of the studies [27,32,33,[37][38][39][40][41][42][43][44]. Direct documentation by research staff was used by three studies (7.5 %) [45][46][47].…”
Section: Resultsmentioning
confidence: 99%
“…Asian patients were most frequently identified as at increased risk for anticoagulantrelated ADEs, including both bleeding events and supratherapeutic anticoagulation: three of the four studies that included this group found that Asian race was assoc i a t e d w i t h an a pp r o x i m at e l y f ou r f o l d r i s k o f anticoagulant-related ADEs. The other study including Asians found that this group might spend less time above therapeutic anticoagulation range (13.5 vs 16.1 % in whites), although this result was not statistically significant [25]. Two studies also found black patients to be at increased risk of anticoagulation-related ADEs compared to white patients, although the magnitude of the potential Fig.…”
Section: Anticoagulant-related Adverse Drug Eventsmentioning
confidence: 91%
“…2 These disparities have been further highlighted in specific healthcare services, including screening for breast and cervical cancer and management of diabetes and anticoagulation control. [3][4][5] Additionally, there are disparities in the rates of diagnosis, morbidity, and mortality in minority populations compared with the same among non-Hispanic whites in cancer, diabetes, heart disease, HIV/AIDS, immunizations, infant mortality, and stroke. 6 Although the reasons for these disparities are not fully understood, the IOM has acknowledged several possible factors that may affect the ways in which healthcare providers deliver care to different populations, including language and cultural differences; distrust of the medical system among minority patients; a lack of minority physicians in clinical practice who may be more culturally sensitized to the needs of minority patients; time limitations imposed by the pressures of clinical practice; and conscious or unconscious biases, prejudices, or negative racial and ethnic stereotypes.…”
Section: Introductionmentioning
confidence: 99%
“…An American study of an anticoagulation clinic found that Hispanic patients, but not Asian patients, who were English speaking spent more time in therapeutic range than those who were not. 7 Other studies did not find differences in stroke care or outcomes based on language barriers, but they may have been underpowered. 14,15 Our study has several strengths to highlight, including a rigorous ascertainment of stroke care and outcomes using uniform definitions and trained abstractors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in previous research, longer lengths of stay and inadequate anticoagulation for such patients have been found. 6,7 The objective of this study was to determine the impact of language barriers on the quality of care and clinical outcomes for acute stroke. We hypothesized that patients with language barriers would have lower quality of care and worse outcomes than those without language barriers.…”
mentioning
confidence: 99%